Reconceptualising Good Faith in Indonesia’s Public-Private Partnership Infrastructure Contracts: A Welfare State Perspective - Anggraeny, Isdian; Simamora, Yohanes Sogar; Kurniawan, Faizal; Wahid, Deny Noer; Hapsari, Dwi Ratna Indri (Legality : Jurnal Ilmiah Hukum, 2026)
This study aimed to reconceptualize good faith in Indonesia's public-private partnership infrastructure contracts from a welfare-state perspective. Public-Private Partnership in Indonesia can accelerate the provision of infrastructure to meet the state's welfare obligations. Still, legally it remains an instrument of public policy, not a transfer of the state's constitutional obligations. Using normative legal methods through legislative and conceptual analysis, as well as limited comparison, this article finds that PPP contracts should be understood as administrative contracts (bestuurscontract) that derive from public authority and are oriented towards service and the public interest. Therefore, good faith should not be viewed merely as a moral norm at the time of signing, but rather as an ongoing obligation and corrective principle (redelijkheid en billijkheid) throughout the project cycle. The normative contribution of this article is a reform model that codifies the obligation of good faith, oriented towards the public interest, in laws and their implementing regulations, including cooperation, disclosure of information, and renegotiation. This aims to prevent abuse of authority, protect the public interest, and strengthen legal accountability for project failures.